2022
DOI: 10.3390/toxics10050199
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mixtures in Household Environments: In Silico Predictions and In Vitro Testing of Potential Joint Action on PPARγ in Human Liver Cells

Abstract: There are thousands of chemicals that humans can be exposed to in their everyday environments, the majority of which are currently understudied and lack substantial testing for potential exposure and toxicity. This study aimed to implement in silico methods to characterize the chemicals that co-occur across chemical and product uses in our everyday household environments that also target a common molecular mediator, thus representing understudied mixtures that may exacerbate toxicity in humans. To detail, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…TNF-α enhances hepatic stellate cells (HSC) survival, immune cells activation and hepatocyte death, all of these are associated with liver fibrosis. So, targeting TNF-α signaling pathway is regarded as a noble approach for the treatment of liver fibrosis (Yang and Seki, et al [6][7][8]). Thalicarpine and 1, 3 Dibenzylisoquinoline were able to inhibit the protein TNF-α and their binding affinity toward TNF-α was more than silymarin.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α enhances hepatic stellate cells (HSC) survival, immune cells activation and hepatocyte death, all of these are associated with liver fibrosis. So, targeting TNF-α signaling pathway is regarded as a noble approach for the treatment of liver fibrosis (Yang and Seki, et al [6][7][8]). Thalicarpine and 1, 3 Dibenzylisoquinoline were able to inhibit the protein TNF-α and their binding affinity toward TNF-α was more than silymarin.…”
Section: Discussionmentioning
confidence: 99%
“…These experts were selected to contribute to the TAME Toolkit based on the following qualifications: Dr. Kyle Roell is the lead Data Analyst for the Institute for Environmental Health Solutions at the University of North Carolina at Chapel Hill (UNC) and is an experienced software developer and programmer with expertise in bioinformatics and statistical genetics ( Zhang et al, 2017 ; Roell et al, 2019 ; Roell et al, 2021 ). Ms. Koval is a graduate student in the UNC Department of Environmental Sciences and Engineering and is contributing towards ongoing studies on human health and the environment ( Ring et al, 2021 ; Carberry et al, 2022 ). Rebecca Boyles is a Director of the Center for Data Modernization Solutions at RTI International.…”
Section: Methodsmentioning
confidence: 99%
“…An equimolar mixture of bisphenols altered intracellular lipid accumulation and mRNA expression of genes and proteins related to adipogenesis in a manner distinct from individual bisphenols, highlighting the need for consideration of the potential cumulative effects of similar chemicals. Using the U.S. Environmental Protection Agency’s Chemical and Products Database (CPDat) and the ToxCast/Tox 21 databases, Carberry et al, 2022 identified benzyl cinnamate, butyl paraben, decanoic acid, eugenol, and sodium dodecyl sulfate as chemicals that co-occur in common exposure sources and target peroxisome proliferator activated receptor gamma (PPARγ) [ 17 ]. They examined the effect of these chemicals individually and in mixtures on PPARγ expression in human liver cells.…”
mentioning
confidence: 99%